Determination Of Vortex Formation At Temenggor Tnb Hydropower Station - Jaafar, Muhamad Aliff Ikmal (Universiti Sains Malaysia, 2021)
The power generated by Temenggor Hydropower station is only 80% of the station’s full capacity. The reason behind this reduced power generation, is due to the formation of free surface vortices at the hydraulic intake. This study is focuses on numerical simulation using ANSYS fluent software. The model was built using SolidWorks and the data were obtained from the dam’s blueprints and LIDAR scanner (Light Detection and Ranging) for the intake topology. The mesh sensitivity analysis was then carried out by testing different element sizes. This study was carried out by simulating the dam water flow using k-epsilon turbulence model and volume of fraction (VOF) at different water level in order to observe the vortices formation at hydraulic intake. The results validation is then carried out by comparing the simulation outlet discharge with the real discharge. The analysis was carried out by comparing the energy level, outlet flow rate and total loss in penstock with respects to different water level. The findings from the simulations and results are, the vortices disrupt the intake flow but with increasing water level the effect reduced. Penstock 4 are affected the most due to vortices consistently form at any water level.